Dental practitioners' attitudes, subjective norms and intentions to practice atraumatic restorative treatment (ART) in Tanzania - Emil N. Kikwilu; Jo E. Frencken; Jan Mulder; Joyce R. Masalu (University of São Paulo, 2009)
The aim of this study was to describe the attitude and subjective norm of dental practitioners towards practicing the atraumatic restorative treatment (ART) in Tanzania. A pre-tested questionnaire on attitudes and subjective norms to practice ART was mailed to all 147 dental practitioners working in the regional and district government clinics. The independent variables were: gender, working experience, qualification and ever heard of ART. The dependent variables were: attitude, subjective norm and intention to practice ART. Chi-square tests and multiple regression analysis were used to test for effects between independent and dependent variables. Significance level was set at 5%. A total of 138 practitioners returned completed questionnaires. More experienced dental practitioners encountered moderate social pressure than less experienced dental practitioners, who met strong social pressure (p=0.045). A total of 73.2% of dental practitioners felt that ART was worth introducing in Tanzania, 92.8% recommended ART training for all dental practitioners and 97.8% recommended inclusion of ART in dental curricula. Positive attitude, strong subjective norm and high intention to practice ART were recorded in 76.3%, 28.1% and 90.6% of the practitioners, respectively. Only subjective norm had a statistically significant influence on the intention to practice ART (p<0.0001). The results indicated that dental practitioners were willing to have ART introduced in Tanzania and had positive attitudes towards practicing this technique. Nevertheless, their intention to perform ART was strongly influenced by social pressures. Therefore, in order to have a successful introduction of ART in Tanzania, people who matter in the daily practice of dental practitioners need to accept and appraise the ART approach positively.